Burden of caregivers and out‐of‐pocket expenditures related to epidermolysis bullosa in France. (7th September 2022) - Bourrat, Emmanuelle; Taieb, Charles; Marquié, Adrien; Causse, Patricia; Bergqvist, Christina; Sauvestre, Angelique; Bellon, Nathalia
Abstract: Introduction and objectives: Inherited epidermolysis bullosa (EB) is a heterogeneous group of genodermatoses characterized by localized or generalized skin and/or mucosal fragility. The objective of this work was to evaluate in France the burden of disease and out‐of‐pocket (OOP) expenditures for families with a child affected by EB. Material and methods: A digital questionnaire was built and distributed to parents of children with EB in partnership with the patients' association DEBRA France. The questionnaire collected clinical and socioeconomic characteristics including the estimated amount of money caregivers had to pay out of their own pockets. The burden of caregivers was assessed using the validated Epidermolysis Bullosa Burden of Disease (EB‐BoD) tool. Linear univariate regression models were conducted to search for factors associated with higher burden and higher OOP. Results: Between October and December 2021, 77 parents answered the questionnaire. The responder was the child's mother in 77% ( n  = 59) of cases. Parents represented 40 girls and 37 boys with a mean age of 7.5 years and with different EB types and disease severity. The mean BE‐BOD score was 63.9 ± 20.2. The mean score observed in children with severe EB was 69.0 ± 21 versus 59.0 ± 18.6 for moderate/mild. Similarly, the mean BE‐BOD scores observed in parents performing daily wound care were 67.9 ± 19.6. All parents (100%) reported OOP expenses. The mean annual OOP cost was 4129€ ± 4321€. Linear regression demonstrated that for each one‐point increase in the EB‐BoD score, OOP expense increases by 91.1 euros (35.1–147) p  = 0.002. Conclusion: EB places a considerable burden on families' daily lives. This burden is closely associated with OOP expenditures to manage EB which were on average 20 times higher compared with the French population.